Penerapan Transaksi Pembayaran Non-Tunai oleh Pelaku Usaha Terhadap Konsumen Ditinjau dari Undang-Undang Nomor 7 Tahun 2011 Tentang Mata Uang dan Hukum Ekonomi Syariah - Rahma Seliati Br Sitorus; Annisa Sativa (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze business actors who take their own actions towards consumers in making payments by not using cash. The development of digital payment systems has made business actors increasingly limit payment methods to non-cash only, thereby reducing consumers' rights to choose their preferred payment method. From the previous explanation, there are several problems in the study, namely regarding how business actors implement non-cash payments to consumers, based on Law Number 7 of 2011 concerning Currency and Islamic economic law. The approach used in this study is a normative legal approach by analyzing statutory and conceptual regulations through a literature review. The results of the discussion indicate that the mandatory implementation of non-cash payments may conflict with the provisions of Law Number 7 of 2011 which regulates the use of the rupiah as an official means of payment. This policy contradicts the basics of Islamic economic law such as willingness and justice ('adl), and freedom of contract because it does not provide choices to consumers. It can be concluded that the implementation carried out by business actors in non-cash transactions needs to be adjusted to applicable legal provisions and sharia principles while still providing cash payment alternatives to ensure fairness and consumer protection.